Serum creatinine measurements: evaluation of a questionnaire according to the ESUR guidelines. (May 2015) - Zähringer, Caroline; Potthast, Silke; Tyndall, Anthony Joseph; Bongartz, Georg; Hohmann, Joachim
Background: The European Society of Urogenital Radiology (ESUR) propose measurements of serum creatinine levels in patients undergoing contrast-enhanced studies with a high probability of impaired renal function and therefore with a higher risk of CIN and NSF. Purpose: To determine whether the recommended questionnaire is able to select these patients. Material and Methods: Over a time period of 10 months the questionnaire was conducted in 1389 patients (725 women, 654 men) before contrast administration for computed tomography (CT) or magnetic resonance imaging (MRI) examination. Serum creatinine (SCr) measurements and calculation of estimated glomerular filtration rate (eGFR) values were performed when one or more answers were positive. Eighty-one patients were excluded due to incomplete data. Statistical evaluation of the questionnaire was done retrospectively. Results: Four hundred and ninety-nine patients (38%) gave one or more positive answers to the questionnaire. Of these, 71 (14%) had an eGFR <60 mL/min/1.73 m 2, 31 (6%) had an eGFR <45 mL/min/1.73 m 2, and five (1%) had an eGFR <30 mL/min/1.73 m 2 . Only the question concerning previous renal disease showed a significant correlation to an eGFR <60 mL/min/1.73 m 2 ( P  < 0.05) and <45 mL/min/1.73 m 2 . Slight correlations with some other risk factors (renal disease, family history of renal disease, arterial hypertension with medication, analgetic medication with nephrotoxic drugs) were found for either a threshold of 60 or 45 mL/min/1.73 m 2 . In addition, there was a positive correlation with patient age. Conclusion: We propose to reduce the questionnaire to a smaller number of risk factors and consider a point-of-care (POC) SCr measurement for all patients aged >70 years without a recent eGFR value while referred for CT. For MRI a SCr measurement is not mandatory while using medium and lowest risk contrast agents.